GAMBARAN PERILAKU SISWI DALAM PEMERIKSAAN PAYUDARA SENDIRI (SADARI) DI SMA PLUS SAFIYYATUL AMALIYYAH MEDAN TAHUN 2012 - masdiana tanjung; Syarifah .; Eddy Syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2012)
ABSTRACT Lifestyle and the times are very important factor in influencing adolescents exposed to risk of breast cancer. Breast cancer can be found at an early stage by means of early detection of the breast self examination (BSE). BSE is an effective and efficient methods for finding breast cancer at an early stage. However, Breast self-exam techniques are not common, just the small number of teenagers who regularly perform breast self-exam every month. This study aims to know the description of student behavior that includes an overview of knowledge, attitudes and actions toward the prevention of breast cancer with breast self-examination (BSE) in High School Plus Safiyyatul amaliyyah. This type of study is a descriptive survey research with a quantitative approach. The population in this study were all high school female student. The number of samples amounted to 45 person, with a purposive sampling technique sampling. The data was collected using a questionnaire as a guide when interview questions. The results showed that most respondents knowledge about BSE categorization that as many as 37 respondents (84.45%), the attitude of the respondents considered good by 41 respondents (91.11%), and measures against BSE categorization of respondents as many as 34 the respondents (75.56%). Based on the results of the study suggested to Medan city health department and other anti-cancer health agencies to adding intensity for information and counseling to young people to take precautionary action for early breast cancer by breast self-examination (BSE). Keywords: Student Behaviors, Breast Self-Examination (BSE), SMA Safiyyatul Amaliyyah